Behavioral and physiological responses to instability in group membership in wild male woolly monkeys (Lagothrix lagotricha poeppigii). Issue 3 (8th February 2021) - Pain, Evelyn L.; Koenig, Andreas; Di Fiore, Anthony; Lu, Amy
Abstract: In group‐living species, integrating into a new social group after dispersal is an important life history milestone associated with physical and social challenges. Generally, this process seems to be accompanied by heightened glucocorticoid (GC) concentrations; however, most studies of physiological responses to group transfer have been conducted on species with despotic social relationships, where integrating individuals are often targets of frequent aggression. Here we present data on fecal glucocorticoid (fGC) concentrations during periods of unstable group membership for male woolly monkeys ( Lagothrix lagotricha poeppigii ), a species with extremely low rates of male–male aggression and generally tolerant male–male associations. We collected data on males in four study groups at the Tiputini Biodiversity Station, Ecuador, and observed three attempted transfer events, involving a total of four adult males, in one study group. We observed only three instances of overt aggression (chases) between males across the entire study period, though male display behaviors were more frequent. We tested whether rates of displays were higher during periods of unstable group membership using a generalized linear mixed model (LMM). We also examined whether male status, group stability, and the occurrence of intergroup encounters affected fGC concentrations using LMMs. Contrary to our predictions, rates of display behaviors were not higher during periods of unstable group membership. However, both transient/integrating males and those who were already group members showed elevated fGC concentrations during these unstable periods. Our results suggest that even in species with tolerant male–male relationships, the integration of unfamiliar individuals can provoke an increase in GCs. Abstract : Log fGC concentrations were higher in male woolly monkeys when group membership was unstable. Research Highlights: Within‐group aggression observed only a few times and toward integrating males. Fecal glucocorticoids were higher for males in periods of unstable group membership. Integrating males did not have higher fecal glucocorticoids than male group members.